A prospective, multicentre survey on antifungal therapy in neutropenic paediatric haematology patients. Issue 1 (19th March 2012) - Cesaro, Simone; Pagano, Livio; Caira, Morena; Carraro, Francesca; Luciani, Matteo; Russo, Delia; Colombini, Antonella; Morello, William; Viale, Pierluigi; Rossi, Giuseppe; Tridello, Gloria; Pegoraro, Anna; et al.
Summary Invasive fungal infections are a frequent complication after intensive chemotherapy. The aims of this prospective study were to describe the use of antifungal therapy and to report which strategy was routinely adopted to guide the introduction of antifungal therapy. A total of 321 febrile episodes in 160 paediatric patients affected by acute leukaemia or non‐Hodgkin‐lymphoma were investigated. Antifungal therapy was used in 100 of 321 febrile episodes (31%), and classified as empiric in 73 episodes, diagnostic‐driven in 25 episodes and targeted in 2 episodes. Switching to a second‐line antifungal therapy was needed in 28 of 100 episodes (28%) and was classified as empiric in 10 episodes (36%), diagnostic‐driven in 17 episodes (61%) and targeted in 1 episode (4%). In 9 of 28 episodes (32%), switching to a third‐line antifungal therapy was performed and was classified as empiric in 2 episodes (22%), diagnostic‐driven in 6 episodes (67%) and targeted in 1 episode (11%). Invasive fungal infections was reported in 23 of 100 episodes: confirmed in 4 episodes, probable in 8 episodes, and possible in 11 episodes. Attributable mortality was 2.8%. Antifungal therapy was still used mostly empirically, whereas as fever persisted, its modification was guided by a diagnostic‐driven approach.